Effects of coated and briquette urea on yield and nitrogen use efficiency of rice at Rampur, Chitwan, Nepal - Marahatta, S. (Journal of Agriculture and Forestry University, 2022)
Nitrogen is one of the most limiting element for the growth and yield of rice. However, the imbalance use of conventional urea leads to loss of nitrogen from rice field, decrease nitrogen use efficiency, increase environmental pollution and cost of cultivation. This study was done to evaluate the response of polymer coated urea (PCU) and urea briquette (UB) on the yield and nitrogen use efficiencies (NUE) of rice on a sandy loam soil. The experiment was conducted at the agronomy research farm of Agriculture and Forestry University during the rainy season of 2018 in a randomized complete block design with three replications for each treatment (T1 - control, 0 kg N ha-1; T2- Prilled urea, 150 kg N ha-1 single application at basal; T3- Prilled urea, 150 kg N ha-1 standard split application; T4-PCU, 150 kg N ha-1 single application at basal; T5-UB, 150 kg N ha-1 single application at basal). The data on yield, and NUE were recorded and analyzed by using R studio. The physical and economic maximum dose of Nitrogen for these different types of urea were also calculated. Compared with single application of Prilled urea (3698 kg ha-1), rice fertilized with Prilled urea with standard split application (4747 kg ha-1), single application of PCU (5183 kg ha-1) and BU (4787 kg ha-1) had significantly higher grain yield and NUE. Economic maximum dose of nitrogen was reduced greatly for the single application of PCU (124 kg N ha-1) compared to Prilled urea with standard split application (167 kg N ha-1). Single application of PCU and UB can be considered as an alternative nitrogen fertilizer for rice even in the sandy loam soil.